THE EU RESPONSE TO THE MASSIVE INFLUX OF DISPLACED PERSONS FROM UKRAINE IN 2022 - Morawska, Elżbieta Hanna (Zeszyty Prawnicze, 2024)
Russia has been conducting military action against Ukraine since 24 February 2022, in violation of the prohibition on the threat or use of violence against the territorial integrity or independence of any state, which is one of the fundamental principles of modern international law. The Russian aggression has resulted in a sharp increase in migratory pressure on the EU. As a result, the Union launched a special temporary protection procedure for the first time in its history. As temporary protection is one of the instruments of the Common European Asylum System, this article begins with an analysis of its nature within EU asylum policy. The article’s next research question and objective relate directly to the EU’s response to the Russian act of aggression. They are relevant for clarifying the political context of the activation of temporary protection and, simultaneously, establishing the circumstances necessary for the activation of temporary protection in the light of Council Directive 2001/55/EC. This Directive and Council Implementing Decision 2022/382 determine the normative construction of the temporary protection 2022. These elements are its duration, the categories of beneficiaries, and the beneficiaries’ entitlements, which result in obligations for Member States. The analysis of these issues will determine to what extent temporary protection is a viable and eﬀective measure of international protection for displaced persons from Ukraine.